2021
DOI: 10.3390/ijerph182111335
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Families’ Leisure, Educational/Work and Social Screen Time Behaviours before and during COVID-19 in Australia: Findings from the Our Life at Home Study

Abstract: This study aimed to understand differences in leisure, educational/work and social screen time behaviours experienced by parents and children due to COVID-19 lockdown restrictions, which may inform behaviour change strategies and policy in the transition to a COVID-normal life. Participants in the “Our Life at Home” study (n = 218 parents from Australia, 43.4 ± 6.8 years, 88% female) completed a cross-sectional online survey in April/May 2020. Parents recalled their own and their child (8.7 ± 2.0 years, 42% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…The findings highlight the numerous and varied challenges that families experience when trying to manage screen time, particularly under COVID-19 lockdown restrictions. Quantitative data has shown that children’s and parents’ screen use increased during lockdown in Australia [ 9 ] and globally [ 10 ]. The current findings provide insights into the current screen time context within homes and suggestions for development of a program to help families manage screen time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings highlight the numerous and varied challenges that families experience when trying to manage screen time, particularly under COVID-19 lockdown restrictions. Quantitative data has shown that children’s and parents’ screen use increased during lockdown in Australia [ 9 ] and globally [ 10 ]. The current findings provide insights into the current screen time context within homes and suggestions for development of a program to help families manage screen time.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 lockdown restrictions implemented in Australia and many countries worldwide saw the closure of schools, recreation and sporting facilities and the implementation of social distancing rules and restrictions. Consequently, schooling and social interactions moved online which led to increased time spent on screens for various reasons [ 9 , 10 ]. Emerging evidence shows that elevated screen time during the COVID pandemic was associated with poorer levels of physical activity and sleep [ 11 ] and poorer mental health and greater perceived stress [ 12 ] amongst youth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the high use of social media (Instagram, Facebook and TikTok) and the low uptake of apps for physical activity among survey participants, as apps remove key social and interactive aspects that girls value [ 28 ]. Use of social media for social connections is also unsurprising as this study was conducted when parts of Australia were coming out of lockdown restrictions due to the coronavirus (COVID-19) pandemic and social communications frequently occurred via digital technologies [ 40 ]. However, our findings add new insights to understanding the digital engagements that that shape girls’ preferences.…”
Section: Discussionmentioning
confidence: 99%
“…They also missed team sport, school trips and visits to the local pool, cinema and library. This resulted in more time in front of screens – an observation many parents made anecdotally, evidenced in news stories [ 2 ] and media surveys around the world [ 3 , 4 ]. At the same time, tracking by Nielsen Bookscan provided intriguing signals that patterns of Australian reading were changing during the pandemic.…”
Section: Introductionmentioning
confidence: 99%